Legal Construction on Training Ship Management Belongs To Human Resources Development Of Transportation (BPSDMP) Based On Dignity Justice Value - Wahyu Wibisono (Universitas Islam Sultan Agung, 2019)
President of the Republic of Indonesia, Joko Widodo stressed that in the coming year human resource development is a key priority in the government program (Nawacita) and focused on three things; positive character development, improvement of access, quality of education, development and match the link between industry and vocational education, one of them by adding a nautical school educational facilities with their training ship. Six (6) training ship construction started in December 2015 and completed in stages over two years to finance multi-year state budget until 2019. And finally Human Resources Development Of Transportation (BPSDMP) Ministry of Transportation in coordination with the Minister of maritime has ordered six (6) units training ship cadets that each measure approximately 1200 GT (Gross Tonnage) with a capacity of 300 people, which is built in harbor and the domestic industry by PT Steadfast Marine Pontianak. Coordinating Minister of Maritime also said that with the training ship would be easier for BPSDM to improve the quality of education Midshipman cruise who were taking education time official the country especially in the field of shipping, including also can help private schools and shipping academy that did not have a training ship for come to enjoy it. So the hope is able to bring high quality graduates and proud when recruited at the national and international shipping companies.Keywords: Legal Construction; Training ship Management; Dignity Justice.